Kebudayaan dan Sastra dalam Perspektif Pascakolonial - Rahariyoso, Dwi (Jurusan Sejarah, Seni, dan Arkeologi, FKIP Universitas Jambi, 2023)
Indonesian culture makes Indonesia a people whose existence has been a locus for centuries. Indonesian culture is a construction that has historically produced a lot of acculturations. Colonial traces, it can be said, are still inherent and contribute to constructing how we view culture specifically. Literature is culturally romanticized in postcolonial studies, as a cultural product and postcolonialism itself is a cultural movement that helps us understand the paradigm landscape and all its implications. Literature can expose the projection of various problems in culture. In the discourse of postcolonialism, literature is used to see the extent to which colonial consciousness is embedded in the writers and readers of literature. This includes the articulation of culture and identity, all of which require critical reflection in relation to the cultural promotion program that is used as a parameter for the progress of the Indonesian nation. Abstrak Kebudayaan Indonesia menjadikan Indonesia sebagai suku bangsa yang ada. Indonesia menjadi suatu lokus berabad silam. kebudayaan Indonesia adalah suatu konstruksi yang secara historis kebanyakan menghasilkan berbagai akulturasi. Jejak kolonial, bisa dikatakan masih inheren dan turut mengonstruksi bagaimana cara pandang kita terhadap kebudayaan secara spesifik. Sastra secara kultural memiliki romantisme dalam kajian pascakolonial, yakni sebagai produk budaya dan pascakolonialisme sendiri merupakan pergerakan kebudayaan yang membantu kita memahami bentang alam paradigma beserta seluruh implikasinya. Sastra dapat mengekspos proyeksi berbagai masalah dalam kebudayaan. Dalam wacana pascakolonialisme, karya sastra digunakan untuk melihat sejauh mana kesadaran kolonial melekat pada diri penulis dan pembaca sastra. Termasuk di dalamnya adalah artikulasi kebudayaan dan identitas yang semuanya membutuhkan suatu refleksi kritis dalam kaitannya dengan program pemajuan kebudayaan yang dijadikan parameter kemajuan bangsa Indonesia.